Somatic ablation of IKKβ in liver and leukocytes is not tolerated in obese mice but hepatic IKKβ deletion improves fatty liver and insulin sensitivity. Issue 9 (24th August 2022) - Silva, Vagner Ramon R.; Molinaro, Angela; Gaudi, Andrea Usseglio; Fryk, Emanuel; Sardi, Claudia; Hammarlund, Maria; Mjörnstedt, Filip; Johansson, Maria E.; Becattini, Barbara; Jansson, Per‐Anders; Solinas, Giovanni
Abstract: The kinase IKKβ controls pro‐inflammatory gene expression, and its activity in the liver and leukocytes was shown to drive metabolic inflammation and insulin resistance in obesity. However, it was also proposed that liver IKKβ signaling protects obese mice from insulin resistance and endoplasmic reticulum (ER) stress by increasing XBP1s protein stability. Furthermore, mice lacking IKKβ in leukocytes display increased lethality to lipopolysaccharides. This study aims at improving our understanding of the role of IKKβ signaling in obesity. We induced IKKβ deletion in hematopoietic cells and liver of obese mice by Cre‐LoxP recombination, using an INF‐inducible system, or a liver‐specific IKKβ deletion in obese mice by adenovirus delivery of the Cre recombinase. The histopathological, immune, and metabolic phenotype of the mice was characterized. IKKβ deletion in the liver and hematopoietic cells was not tolerated in mice with established obesity exposed to the TLR3 agonist poly(I:C) and exacerbated liver damage and ER‐stress despite elevated XBP1s. By contrast, liver‐specific ablation of IKKβ in obese mice reduced steatosis and improved insulin sensitivity in association with increased XBP1s protein abundance and reduced expression of de‐novo lipogenesis genes. We conclude that IKKβ blockage in liver and leukocytes is not tolerated in obese mice exposed to TLR3 agonists. However, selective hepatic IKKβ ablation improves fatty liver and insulin sensitivity in association with increased XBP1s protein abundance and reduced expression of lipogenic genes.